Towards a green future : Nordic Climate Solutions (Copenhagen : Nordic Council of Ministers, 2009)
Content Grant Financing for Climate Efforts Nefco Expects Copenhagen Summit to Support Efficient and Effective Carbon Markets Climate Needs Money in Good Times and Bad Research, the Key to Sustainable Energy Solutions Clean, Clever & Competitive Coping with Climate Change North Atlantic Perspectives on Climate Change Genetic Resources and the Environment A Territorial Approach